METABOLITE PRODUCTS, ACIDITY AND DIGESTABILITY IN-VITRO LITTER BROILER FERMENTED BY LIGNOCELLULOLYTIC BACTERIA - A. B., Bangun; Mudita, I M.; Puspani, E. (Jurnal Peternakan Tropika, 2022)
This study aims to determine the metabolite products, acidity and digestibility in vitro from litter broiler fermented by lignocellulolytic bacteria. The study was carried out in Closed house and the Nutrition and Animal Feed Laboratory of the Faculty of Animal Husbandry, Udayana University which was carried out from November to December 2021. The design used was a completely randomized design (CRD) consisting of 6 treatments, namely without lignocellulolytic bacterial fermentation as control (PB0), using bacterial fermentation of Bacillus substilis BR4LG (PB1), using bacterial fermentation of Bacillus substilis BR2CL (PB2), using bacterial fermentation of Aneurinibacillus sp. BT4LS (PB3), using bacterial fermentation of Bacillus sp. BT3CL (PB4), and using bacterial fermentation Bacillus sp. BT8XY (PB5). Each treatment had 4 replications. The variables observed were digestibility (KcBK and KcBO), metabolite products (VFA and NH3) and the degree of acidity (pH). Data were analyzed using variance. The results showed that the Bacillus substilis BR2CL (PB2) treatment resulted in the lowest pH value of 6.57 (P<0.05) against PB0 (control). Treatment of Bacillus sp. BT3CL (PB4) produced the highest N-NH3 of 6.84 mM (P<0.05) against PB0 (control). Treatment of Bacillus sp. BT8XY (PB5) resulted in the highest total KcBK, KcBO and VFA respectively at 62.98 %, 66.76 %BK and 138.84 Mm (P<0.05) against PB0 (control). Based on the results of the study, it can be concluded that the use of lignocellulolytic bacteria was able to increase the digestibility of dry matter and organic matter, metabolite products (VFA and N-NH3) as well as the degree of acidity in vitro from litter broilerThe best lignocellulolytic bacteria in this study was Bacillus sp. BT8XY produces the highest KcBK, KcBO and VFA values. Keywords: lignocellulolytic bacteria, litter broiler, metabolite products, acidity and digestibility in-vitro